Predictors of Resectability and Survival in Patients With Borderline and Locally Advanced Pancreatic Cancer who Underwent Neoadjuvant Treatment With FOLFIRINOX. Issue 4 (April 2019) - Michelakos, Theodoros; Pergolini, Ilaria; Castillo, Carlos Fernández-del; Honselmann, Kim C.; Cai, Lei; Deshpande, Vikram; Wo, Jennifer Y.; Ryan, David P.; Allen, Jill N.; Blaszkowsky, Lawrence S.; Clark, Jeffrey W.; Murphy, Janet E.; et al.
Abstract : Objective: The aim of this study was to determine (1) whether preoperative factors can predict resectability of borderline resectable (BR) and locally advanced (LA) pancreatic ductal adenocarcinoma (PDAC) after neoadjuvant FOLFIRINOX, (2) which patients might benefit from adjuvant therapy, and (3) survival differences between resected BR/LA patients who received neoadjuvant FOLFIRINOX and upfront resected patients. Background: Patients with BR/LA PDAC are often treated with FOLFIRINOX to obtain a margin-negative resection, yet selection of patients for resection remains challenging. Methods: Clinicopathologic data of PDAC patients surgically explored between 04/2011-11/2016 in a single institution were retrospectively collected. Results: Following neoadjuvant FOLFIRINOX, 141 patients were surgically explored (BR: 49%, LA: 51%) and 110 (78%) were resected. Resected patients had lower preoperative CA 19-9 levels (21 vs 40 U/mL, P = 0.03) and smaller tumors on preoperative computed tomography (CT) scan (2.3 vs 3.0 cm, P = 0.03), but no predictors of resectability were identified. Median overall survival (OS) was 34.2 months from diagnosis for all FOLFIRINOX patients and 37.7 months for resected patients. Among resected patients, preoperative CA 19-9 >100 U/mL and >8 months between diagnosis and surgery predicted a shorter postoperative disease-free survival (DFS); Charlson comorbidity index >1, preoperative CA 19-9 >100 U/mL and tumor size (>3.0 cm on CT or >2.5 cm on pathology) predicted decreased OS. DFS and OS were significantly better for BR/LA PDAC patients treated with neoadjuvant FOLFIRINOX compared with upfront resected patients (DFS: 29.1 vs 13.7, P < 0.001; OS: 37.7 vs 25.1 months from diagnosis, P = 0.01). Conclusion: BR/LA PDAC patients with no progression on neoadjuvant FOLFIRINOX should be offered surgical exploration. Except size, traditional pathological parameters fail to predict survival among resected FOLFIRINOX patients. Resected FOLFIRINOX patients have survival that appears to be superior than that of resectable patients who go directly to surgery. Abstract : Supplemental Digital Content is available in the text